PERMAINAN GERAK IRAMA TERHADAP KEMAMPUAN MENGENAL ARAH ANAK TUNAGRAHITA RINGAN DI SLB - Muzarofah, Riski (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   This research was formed background by the importance to recognize direction to mild mentally retardation children so they were not wrong in interpreting the command. Mild mentally retardation children had so low intellectual ability that it made them find difficulty in thinking an abstract concept including the direction concept. As the children generally, the mild mentally retardation children were also interested in games. Therefore, to develop recognizing direction ability the mild mentally retardation children were used rhythm movement game. This research was limited in recognizing right and left, and front and back directions through game with involving the part of body such as right and left hands. This research had purpose to prove the influence of rhythm movement game toward recognizing direction ability to mild mentally retardation children in SLB Al-Chusnaini Sidoarjo. The kind of the research used was pre-experiment. The research design used one group pretest and post test. The subjects in this research were the first class of mild mentally retardation children in SLB Al-Chusnaini Sidoarjo. The technique used for collecting data was observation and action test. The data analysis used statistic non parametric with sign test. The research result indicated that there was value enhancement of recognizing direction ability between pre-test and post-test. The result of data analysis indicated that ZH = 2,04 > + 1,96 this meant that there was influence of rhythm movement game toward recognizing direction ability to mild mentally retardation children in SLB Al-Chusnaini Sidoarjo.     Keywords: rhythm movement game, direction